Influence of Nollywood Films Representation of the Elderly in Nigeria - Subulola Etimiri (Lakhomi Journal Scientific Journal of Culture, 2024)
The influence of Nollywood films on the representation of the elderly in Nigeria is a topic of significant cultural and social importance. Nollywood, the Nigerian film industry, is one of the largest and most prolific film industries in the world. With its diverse range of genres, Nollywood films have a profound impact on shaping societal views, especially concerning the elderly. Nollywood films often portray elderly characters in roles that reflect traditional Nigerian values. These films typically show older individuals as wise, respected members of the community, who provide guidance and spiritual leadership to younger generations. In many cases, elders are depicted as the moral compass of the family, helping to resolve conflicts and uphold traditional values. However, there is also a contrasting portrayal where the elderly people are seen as weak, helpless, or sometimes even villainous. Some films depict elderly characters as scheming or greedy, particularly in family dynamics involving inheritance or power struggles. This dual representation can influence the perception of the elderly, either affirming their revered status or challenging it. Nollywood films often highlight issues related to aging, such as health problems, physical decline, and the challenges of growing old in a rapidly changing society. While these depictions can raise awareness about the needs and struggles of the elderly, they sometimes present negative stereotypes, such as portraying elderly people as burdens on the family or society. This can shape how younger generations view aging, often emphasizing fear or avoidance of growing old.